Disaster risk management through gendered vulnerability and mainstreaming - Sneh Gangwar (National Geographical Journal of India, 2024)
The significant losses in human life and livelihoods, the destruction of economic and social infrastructure and damage to the environment caused by disasters in the past decade has increased the necessity for proper disaster reduction and risk management strategies. A disaster is shown as a combination of a trigger agent and vulnerabilities. Since vulnerabilities are the dependent component of a disaster, they should be managed and minimized in order to reduce disasters. Disaster reduction policies and measures, which ensure a decrease in vulnerabilities, need to be formed and implemented to achieve a sustainable and consistent plan of disaster management. Since women are more vulnerable in a disaster, their needs and concerns should be widely integrated into risk reduction plans and procedures from both perspectives of women as beneficiaries and decision makers. Gender mainstreaming is considered an important element in disaster reduction policy making to integrate a gender equality perspective in all policies at all levels. Gender mainstreaming in disaster reduction refers to promoting awareness about gender equity and equality, to help reduce the impact of disasters and to incorporate gender analysis in disaster management, risk reduction and sustainable development to decrease vulnerability. The paper emphasise the importance of one of the perspectives less considered in most of the studies about risk and disasters, i.e. differentiated experience of men and women during the occurrence of disaster as a result of their gender. This paper also gives an account of the gender mainstreaming, its importance and proposed means of integrating it into disaster reduction policies and measures. This paper is based on a review of academic literature, papers and reports produced by various institutes, NGOs, Government organizations etc.